2011
DOI: 10.2196/jmir.1560
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Support on Facebook: A Content Analysis of Breast Cancer Groups

Abstract: BackgroundSocial network sites have been growing in popularity across broad segments of Internet users, and are a convenient means to exchange information and support. Research on their use for health-related purposes is limited.ObjectiveThis study aimed to characterize the purpose, use, and creators of Facebook groups related to breast cancer.MethodsWe searched Facebook (www.Facebook.com) using the term breast cancer. We restricted our analysis to groups that were related to breast cancer, operated in English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
257
1
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(286 citation statements)
references
References 32 publications
(43 reference statements)
6
257
1
11
Order By: Relevance
“…Although these were raised by a minority of respondents, this theme was recurrent within these responses. This is consistent with perspectives on support as a "mixed blessing" (12) , and suggests that formal support groups can inadvertently facilitate patients focusing on negative aspects of their illness.…”
Section: Support Group Factorssupporting
confidence: 79%
See 1 more Smart Citation
“…Although these were raised by a minority of respondents, this theme was recurrent within these responses. This is consistent with perspectives on support as a "mixed blessing" (12) , and suggests that formal support groups can inadvertently facilitate patients focusing on negative aspects of their illness.…”
Section: Support Group Factorssupporting
confidence: 79%
“…However, besides this, no study has examined formal support groups as sources of potentially beneficial support for individuals with SLE, despite the likelihood that access to support groups has likely improved since Corcoran's study was conducted. Firstly, new support organisations have been founded (e.g., Lupus Group Ireland [2011]), and secondly, the use of social media to facilitate support networks for coping with illness has increased [12].…”
mentioning
confidence: 99%
“…Many websites have multiple communities. In a separate study, we identified over 600 breast cancer groups on Facebook alone [20]. Likewise, the review conducted in 2003 that identified 546 online cancer communities reported all of the 150 mailing lists offered by the Association of Online Cancer Resources at that time [14], a website included in our review.…”
Section: Discussionmentioning
confidence: 99%
“…Estas redes facilitan la interacción de personas con la misma enfermedad, permitiendo que compartan dudas, experiencias y consejos; además de apoyarse y alentarse mutuamente. Estos grupos también pueden contar con profesionales de la salud para resolver dudas y verificar la veracidad de la información 3 .…”
Section: Sr Editorunclassified
“…Se han publicado experiencias positivas sobre grupos creados para Cáncer de mama 3 , alimentación saludable 4 , Diabetes y Cáncer colorrectal 5 .…”
Section: Sr Editorunclassified